Challenging infections in pregnancy (2020)
Maternal sepsis is “a life-threatening condition defined as organ dysfunction resulting from infection during pregnancy, childbirth, post-abortion, or postpartum period.” (World Health Organisation, 2017). Serious infection during, or immediately after, pregnancy may go initially unrecognized in an otherwise young and healthy group, who nevertheless do have a compromized immune system. Secondly, whilst malaise, flushes, nausea, vomiting and abdominal pain are common in pregnancy, each can herald sepsis with rapid demise for mother and baby. The MBRRACE-UK report in 20171 found an overall sepsis-related maternal mortality rate of 0.56 per 100,000 maternities with a mortality rate from genital tract sepsis of 0.28 per 100,000 maternities. This review will focus on the major causes, recognition, differentiation and microbiological management of sepsis in pregnancy, using two detailed cases to illustrate.